Study of multipion production in np-interaction at intermediate energies - Jerusalimov Alexander; Arakelian Susanna; Belyaev Alexander; Ladygin Vladimir; Troyan Alexander (EPJ Web of Conferences, 2019)
The reactions of the multipion production in np-interactions were studied at the momenta of incident neutrons from 1.73 to 5.20 GeV/c. The pions multiplicity of the studied reactions was from 2 to 6. It was shown that the characteristics of the reactions were satisfactory described within the framework of OPER-model (One Pion Reggeizied Exchange). Additionally the diagrams of one baryon exchange (OBE) were used for a better description of the data at the momenta of incident neutrons below 3 GeV/c.